2022
DOI: 10.1021/acs.molpharmaceut.2c00156
|View full text |Cite
|
Sign up to set email alerts
|

Surfactants Accelerate Crystallization of Amorphous Nifedipine by Similar Enhancement of Nucleation and Growth Independent of Hydrophilic–Lipophilic Balance

Abstract: Amorphous formulations, increasingly employed to deliver poorly soluble drugs, generally contain surfactants to improve wetting and dissolution. These surfactants are often liquids and can potentially increase the mobility of the drug and reduce its stability, but little is known about this effect. Here we investigate the effect of four common nonionic surfactants (Tween 80, Span 80, Triton X-100, and Poloxamer 407) on the crystallization of amorphous nifedipine (NIF). We find that the surfactants significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Given Span 20 is usually a viscous liquid at room temperature, which could accelerate crystallization and facilitate molecular mobility in ASD formulations [ 21 ]; therefore, the T g values of milled extrudates and precipitates were measured. Since the heating and cooling ramps of cyclic DSC curves were applied under a dry nitrogen atmosphere, the effect of moisture content on T g was also excluded as much as possible.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given Span 20 is usually a viscous liquid at room temperature, which could accelerate crystallization and facilitate molecular mobility in ASD formulations [ 21 ]; therefore, the T g values of milled extrudates and precipitates were measured. Since the heating and cooling ramps of cyclic DSC curves were applied under a dry nitrogen atmosphere, the effect of moisture content on T g was also excluded as much as possible.…”
Section: Resultsmentioning
confidence: 99%
“…However, Fule et al reported that although itraconazole by itself was miscible with Soluplus up to 40% w / w , the presence of Poloxamer drastically reduced its miscibility to <10% [ 20 ]. A few researches meanwhile reported that the addition of surfactants could strongly affect the inhibition of drug crystallization and the maintenance of supersaturation [ 21 ]. Although adsorption of polymers could inhibit crystal growth by blocking new growth unit incorporation sites [ 22 ], the presence of surfactants in the supersaturation solution usually reduces the adsorption of polymer molecules at the solid interface [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amorphous solid dispersions (ASDs) are increasingly used to improve the bioavailability of poorly water-soluble drugs. However, crystallization must be managed in order to take full advantage of this formulation strategy. For that purpose, ASDs commonly contain polymers , and/or surfactants. In the presence/absence of such excipients, the crystallization kinetics of drugs from the amorphous state has been intensely studied both on storage , and during dissolution. …”
Section: Introductionmentioning
confidence: 99%
“…Span 80 was added to enhance mobility and thus crystal growth rate of RTV in the molten state. [25] A small amount of RTV/Span was placed on a glass coverslip and melted at 403 K. The melt droplet was then cooled to 373 K and seeded with Form III crystal. Afterwards, the droplet was heated to ~ 388 K until one crystal piece was left as the perfect seed.…”
Section: Introductionmentioning
confidence: 99%